SELECTION OF VALUABLE WALNUT GENOTYPES IN THE GENE POOL COLLECTIONS OF VŠÚO HOLOVOUSY [VÝBĚR CENNÝCH GENOTYPŮ VLAŠSKÉHO OŘECHU V GENOFONDOVÝCH SBÍRKÁCH VŠÚO HOLOVOUSY] - Liliia Pavliuk; Michaela Marklová; Boris Krška; Pavel Pech (Vědecké Práce Ovocnářské)
The Persian walnut (Juglans regia L.) is not widely represented in commercial orchards in the Czech Republic, despite its significant potential and lower cultivation requirements compared to other fruit species. The aim of this study was to examine the pomological traits of selected cultivars, focusing on nut and kernel weight, shell thickness and cohesion, and ease of cracking. The correlation between these pomological traits was determined, and the results obtained may be useful for breeding, cultivation, and fruit quality evaluation.